Solder alloy, solder paste, solder ball, solder preform, solder joint, in-vehicle electronic circuit, ECU electronic circuit, in-vehicle electronic circuit device, and ECU electronic circuit device

JP7640921B1Active Publication Date: 2025-03-06SENJU METAL IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024118269
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-03-06
Estimated Expiration
2044-07-23

AI Technical Summary

Benefits of technology

【0023】 これは、特許文献1に記載の発明においては、Biは特許文献1に記載の発明の効果を阻害しない程度に含有してもよい、とされているためであると考えられる。また、濡れ性向上の効果が望まれていなかったためであるとも考えられる。さらに、特許文献1に記載の発明では、Biを含有する場合にはAgの含有量が制限されるため、特許文献1に記載の発明の効果が発揮されない懸念がある。これらを鑑み、本発明者らは、特許文献1に開示されているはんだ合金において、Biを添加する必要があることに着目した。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640921000001_ABST
    Figure 0007640921000001_ABST
Patent Text Reader

Abstract

The present invention provides a solder alloy, solder paste, solder balls, solder preforms, solder joints, on-vehicle electronic circuits, ECU electronic circuits, on-vehicle electronic circuit devices, and ECU electronic circuit devices, which have excellent reliability due to a liquidus temperature that is not too high, high tensile strength, low surface tension of molten solder, and high tensile strength after aging. [Solution] The solder alloy has an alloy composition, by mass%, of 3.0-4.0% Ag, 0.1-1.0% Cu, 3.1-6.0% Sb, 0.1-1.5% Bi, 0.2-6.0% In, 0.02-0.07% Ni, 0.0010-0.0200% Co, and the balance being Sn. Preferably, the alloy composition further contains, by mass%, 0.1% or less in total of at least one of Ge, Ga, As, Pd, Mn, Zn, Zr, and Mg.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solder alloy, a solder paste, a solder ball, a solder preform, a solder joint, an on-vehicle electronic circuit, an ECU electronic circuit, an on-vehicle electronic circuit device, and an ECU electronic circuit device. [Background technology]

[0002] Automobiles are equipped with on-board electronic circuits used in devices that electrically control the engine, power steering, brakes, etc. On-board electronic circuits are extremely important safety components for the operation of an automobile. In particular, on-board electronic circuits called ECUs (Engine Control Units), which are electronic circuits that control the vehicle via computer to improve fuel efficiency, must be able to operate stably without failure for long periods of time. These ECUs are generally installed near the engine, which means that they are used in fairly harsh environments.

[0003] The area near the engine where such on-board electronic circuits are installed becomes extremely hot, at over 125°C, when the engine is running. On the other hand, when the engine is stopped, the outside air temperature drops to a low temperature of -40°C or lower in winter in cold regions such as North America and Siberia. Therefore, the on-board electronic circuits are exposed to a heat cycle environment of at least -40°C to +125°C as the engine is repeatedly started and stopped.

[0004] An in-vehicle electronic circuit is an electronic circuit in which electronic components are soldered to a printed circuit board. The linear thermal expansion coefficient of electronic components and that of printed circuit boards are significantly different. When an in-vehicle electronic circuit is exposed to a heat cycle environment, the electronic components and printed circuit boards each undergo repeated thermal expansion and contraction. This repetition repeatedly generates a certain amount of thermal displacement at the soldered joints (hereinafter referred to as "solder joints") that join the electronic components and printed circuit boards. For this reason, in a heat cycle environment, stress continues to be applied to the solder joints, and eventually the solder joints break.

[0005] Even if the solder joint does not break completely, if it breaks partially, the resistance of the electronic circuit increases, which can cause malfunction. Malfunction of the ECU installed in a car can lead to a serious accident. Thus, improving heat cycle resistance is particularly important in order to prevent ECU malfunction.

[0006] Therefore, Patent Document 1 discloses a solder alloy having heat cycle resistance properties, which is Sn-Ag-Cu-Sb-Ni and contains optional elements In and Co. Patent Document 2 also discloses a solder alloy having heat cycle resistance properties, which is Sn-Ag-Cu-Bi-Ni-Co and contains optional elements Sb and In. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6275178 [Patent Document 2] Patent No. 5349703 Summary of the Invention [Problem to be solved by the invention]

[0008] Paragraph 0008 of Patent Document 1 states that lead-free solder alloys that are strengthened by adding Bi have the disadvantages of poor ductility and increased brittleness. The same paragraph also discloses that when a solder joint is made using a conventional lead-free solder alloy containing added Bi and placed in an environment with large temperature differences, cracks occur in the fillet portion on the chip resistor component side in the longitudinal direction of the chip resistor component.

[0009] Paragraphs 0026 and 0027 of Patent Document 1 state that a part of the crystal lattice of Sn is replaced with Sb, and SnSb is finely dispersed in the Sn grain boundaries even when exposed to an environment with large temperature differences, so that coarsening of Sn crystals is suppressed. Meanwhile, paragraph 0042 of Patent Document 1 states that Bi and the like can be contained within a range that does not impair the effects of the invention described in Patent Document 1.

[0010] However, as mentioned above, Patent Document 1 discloses a Sn-Ag-Cu-Sb-In-Ni-Co solder alloy, but does not disclose a solder alloy containing Bi. The range of the Bi content is not specified. And, in paragraph 0038 of the same document, formula (B) is disclosed, which assumes an alloy composition containing Bi.

[0011] According to formula (B), the Ag content in the case of containing Bi is a maximum of 2.55 mass%. Therefore, in the invention described in Patent Document 1, when a solder alloy containing Bi is assumed, the Ag content is limited. Furthermore, in the same document, solder alloys with an Ag content of 2.55 mass% or less are only disclosed in the reference examples and comparative examples. Therefore, it is proven that the invention described in Patent Document 1 does not provide sufficient heat cycle resistance even when Bi is contained.

[0012] As described in paragraph 0010 of Patent Document 2, the invention described in the same document is said to have a low melting point, excellent mechanical properties such as durability, crack resistance, and erosion resistance, and can suppress the occurrence of voids. In addition, paragraphs 0036, 0039, and 0054 of the same document state that the solder structure can be refined by containing predetermined amounts of Ni, Co, and In.

[0013] However, the melting point is not evaluated in the invention described in Patent Document 2. Also, according to paragraphs 0105, 0106, Table 4 of paragraph 0123, and Table 5 of paragraph 0124 of the same document, it is evaluated that the solder structure can be fined if the maximum structure is less than 50 μm and 50 to 100 μm.

[0014] However, in recent years, global warming has progressed and the maximum temperature has risen, making the usage environment even more severe. On the other hand, even in cold regions, although there is the effect of global warming, temperatures can still drop below -40°C, just as they did before. For this reason, in addition to the solder alloy described in Patent Document 2, there is a demand for solder alloys that are specialized in improving heat cycle resistance.

[0015] Here, it is believed that the heat cycle resistance is improved by suppressing the fracture of the solder joint. Here, in areas with large temperature differences, it is believed that the solder joint is subjected to repeated alternating tensile and compressive stresses due to the difference in thermal expansion coefficient between the solder alloy and the electrodes that make up the solder joint. For this reason, if the solder joint is continuously exposed to a harsh usage environment, it will fracture.

[0016] In order to prevent the solder joint from breaking even if it is continuously exposed to the above-mentioned harsh environment, the solder joint must have a property that prevents the solder joint from breaking at least before the cycle test. Moreover, it is preferable that such a property does not depend on, for example, the electrodes that constitute the solder joint, but is a property that is specific to the solder alloy.

[0017] In order to suppress the deformation of the solder alloy, for example, the tensile strength of the solder alloy can be improved. It is believed that a high tensile strength suppresses the deformation of the solder alloy constituting the solder joint, thereby suppressing the fracture of the solder joint.

[0018] In addition, tests using, for example, the meniscograph method have been used to evaluate the wettability of molten solder. However, in tests using the meniscograph, a copper plate is usually used, so the evaluation of wettability depends on the surface properties of the copper plate, and the time and stress required for wettability to be complete are measured as indicators of wettability. This method is greatly affected by the surface properties of the base material, making it difficult to evaluate wettability precisely. Therefore, the surface tension of a droplet of molten solder can be used as a means of evaluating the wettability specific to solder alloys. This makes it possible to evaluate the wettability specific to solder alloys without depending on the surface properties of the copper plate or other materials.

[0019] Furthermore, since the reflow temperature of the conventionally used Sn-3Ag-0.5Cu solder alloy is 235 to 240°C, when a component with a large heat capacity is used, it may be necessary to perform reflow soldering at the higher temperature side of the above temperature range. In addition, as electronic devices become more powerful, the amount of current flowing increases, and there is a concern that electronic components may heat up. Even if the electronic device heats up, the solder joint must not break. For this reason, solder alloys are also required to have a structure that does not coarsen in a high-temperature environment.

[0020] Therefore, an object of the present invention is to provide a solder alloy, solder paste, solder balls, solder preforms, solder joints, on-vehicle electronic circuits, ECU electronic circuits, on-vehicle electronic circuit devices, and ECU electronic circuit devices, which have excellent reliability due to their not too high liquidus temperature, high tensile strength, low surface tension of molten solder, and high tensile strength after aging. [Means for solving the problem]

[0021] The present inventors have reexamined the solder alloys specifically disclosed in Patent Document 1 and Patent Document 2. As the solder alloys disclosed in Patent Document 1, the inventors have examined the Sn-3.0Ag-0.5Cu-4.0Sb-3.0In-0.03Ni-0.008Co solder alloy (numbers represent mass%) disclosed in Example 16 of Patent Document 1, and the Sn-3.0Ag-0.5Cu-4.0Sb-6.0In-0.03Ni-0.008Co solder alloy (numbers represent mass%) disclosed in Example 17 of Patent Document 1.

[0022] These solder alloys do not contain Bi, so there is no concern about embrittlement, but they cannot achieve significant solid solution strengthening of Sn. In and Sb are also solid solution strengthening elements, but they also have precipitation strengthening aspects, so they cannot achieve solid solution strengthening to the same extent as Bi. As a result, it has been found that tensile strength decreases when exposed to high temperature environments. It has also been found that the surface tension of molten solder is high because they do not contain Bi. It has also been found that the same results are obtained when a small amount of Bi is added.

[0023] This is believed to be because the invention described in Patent Document 1 states that Bi may be contained to the extent that it does not impair the effects of the invention described in Patent Document 1. It is also believed to be because the effect of improving wettability was not desired. Furthermore, in the invention described in Patent Document 1, the Ag content is limited when Bi is contained, so there is a concern that the effects of the invention described in Patent Document 1 will not be achieved. In view of these, the present inventors have focused on the need to add Bi to the solder alloy disclosed in Patent Document 1.

[0024] Patent Document 2 specifically discloses a Sn-Ag-Cu-Bi-Sb-In-Ni-Co solder alloy containing Bi. In this alloy system, attention was paid to the properties of the solder alloy that suppress the rise in melting point and contribute to heat cycle resistance. Then, an alloy composition that shows high tensile strength and tensile strength in a high temperature environment was studied. In such a solder alloy, Bi improves wettability but does not form a compound. For this reason, if the Bi content is high, it is easy to form a low melting point phase, which may impair reliability, so the Bi content needs to be reduced.

[0025] However, as described above, solder alloys with a low Bi content or solder alloys that do not contain Bi as disclosed in Patent Document 1 tend to have a decreased tensile strength when exposed to high temperature environments. Therefore, it is necessary to increase the Sb content to compensate for this. An example of such a solder alloy is the Sn-3.0Ag-0.5Cu-1.0Bi-3.0Sb-4.3In-0.05Ni-0.005Co solder alloy (numbers represent mass%) disclosed in Example 37 of Patent Document 2.

[0026] This solder alloy has a reduced Bi content and a relatively high Sb content among the solder alloys disclosed in Patent Document 2. However, it has been found that even in this solder alloy, the reduced Bi content means that the solid solution strengthening of Sb and the precipitation strengthening of SnSb are insufficient, and the tensile strength deteriorates when exposed to a high-temperature environment.

[0027] Thus, in the Sn-Ag-Cu-Bi-Sb-In-Ni-Co solder alloy, it is necessary to reduce the Bi content as in the past and to include more Sb than in the past. On the other hand, if the Sb content is too high, the above-mentioned problems will occur. For this reason, the Sb content needs to be within an appropriate range.

[0028] In addition, Ag, Cu, Ni, and Co also form compounds with Sn, and the fine precipitation of these compounds contributes to improving wettability. It is believed that the fine precipitation of these compounds can improve tensile strength and tensile strength after exposure to high temperature environments.

[0029] The inventors of the present invention did not focus only on Bi and Sb, but investigated the contents of the constituent elements that form the compound with high precision. As a result, they obtained the knowledge that the tensile strength of the solder alloy is improved, the surface tension of the molten solder itself is reduced, and the tensile strength after exposure to a high-temperature environment (hereinafter referred to as "aging") is also improved, and thus the present invention was completed. Note that, although the present invention has been exemplified with respect to electronic circuits, the present invention is not limited to this as long as it is an application that requires the simultaneous exertion of these effects. The present invention, which was made based on these findings, is as follows.

[0030] (0) A solder alloy comprising, by mass%, 3.0-4.0% Ag, 0.1-1.0% Cu, 3.1-6.0% Sb, 0.1-1.5% Bi, 0.2-6.0% In, 0.02-0.07% Ni, 0.0010-0.0200% Co, and the remainder being Sn. (1) A solder alloy having an alloy composition, in mass%, of 3.0-4.0% Ag, 0.1-1.0% Cu, 3.1-6.0% Sb, 0.1-1.5% Bi, 0.2-6.0% In, 0.02-0.07% Ni, 0.0010-0.0200% Co, and the remainder being Sn.

[0031] (2) The solder alloy according to (0) or (1) above, wherein the alloy composition (solder alloy) further contains, by mass%, 0.1% or less in total of at least one of Ge, Ga, As, Pd, Mn, Zn, Zr, and Mg.

[0032] (3) A solder alloy according to any one of (0) to (2) above, the alloy composition (solder alloy) satisfying the following formulae (1) to (4): 0.00029≦Sb×Ni×Co / (Cu×Bi×In)≦0.00151 (1) 0.0039≦Ag×Cu×Sb×In×Ni×Co / Bi≦0.0332 (2) 4.0≦Cu×Sb×In≦20.0 (3) 265≦Ag×Sb / Ni≦499 (4) In the above formulas (1) to (4), Ag, Cu, Bi, Sb, In, Ni, and Co each represent the content (mass %) of the alloy composition.

[0033] (4) A solder paste comprising a solder powder made of the solder alloy according to any one of (0) to (3) above.

[0034] (5) A solder ball made of the solder alloy according to any one of (0) to (3) above.

[0035] (6) A solder preform made of the solder alloy according to any one of (0) to (3) above.

[0036] (7) A solder joint comprising the solder alloy according to any one of (0) to (3) above.

[0037] (8) An on-vehicle electronic circuit comprising the solder alloy according to any one of (0) to (3) above.

[0038] (9) An ECU electronic circuit comprising the solder alloy according to any one of (0) to (3) above.

[0039] (10) An on-vehicle electronic circuit device comprising the on-vehicle electronic circuit according to (8) above.

[0040] (11) An ECU electronic circuit device comprising the ECU electronic circuit described in (9) above. [Brief description of the drawings]

[0041] [Figure 1] FIG. 1 is a SEM photograph of a cross section after a tensile strength test, enlarged 1000 times, where FIG. 1(a) is Comparative Example 12, FIG. 1(b) is Example 3, and FIG. [Diagram 2]2A to 2C are SEM photographs of FIG. 1 enlarged 3000 times, where FIG. 2A is Comparative Example 12, FIG. 2B is Example 3, and FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] The present invention will be described in more detail below. In this specification, "%" relating to the solder alloy composition is "mass %" unless otherwise specified.

[0043] 1. Solder Alloy (1) Ag: 3.0-4.0% Ag forms a network structure of Ag3Sn, which contributes to improving the tensile strength after aging. If the Ag content exceeds 4.0%, coarse Ag3Sn is formed, and the toughness of the solder alloy decreases, resulting in a decrease in the tensile strength after aging. The upper limit of the Ag content is 4.0% or less, preferably 3.8% or less, more preferably 3.7% or less, and even more preferably 3.6% or less.

[0044] On the other hand, if the Ag content is less than 3.0%, the Ag3Sn network structure is not formed, and the tensile strength after aging decreases. The lower limit of the Ag content is 3.0% or more, preferably 3.1% or more, more preferably 3.2% or more, even more preferably 3.3% or more, and particularly preferably 3.4% or more. The preferred range of Ag is 3.2 to 3.6%.

[0045] (2) Cu: 0.1-1.0% Cu reduces surface tension and improves tensile strength and tensile strength after aging by precipitation strengthening. If the Cu content exceeds 1.0%, coarse Cu6Sn5 is formed, so that the tensile strength after aging decreases. The upper limit of the Cu content is 1.0% or less, preferably 0.9% or less, more preferably 0.8% or less, and further preferably 0.7% or less.

[0046] On the other hand, if the Cu content is less than 0.1%, the compound with Sn does not precipitate sufficiently, resulting in poor surface tension, and therefore poor tensile strength and tensile strength after aging. The lower limit of the Cu content is 0.1% or more, preferably 0.3% or more, more preferably 0.5% or more, and even more preferably 0.6% or more. The preferred range of Cu is 0.5 to 0.9%.

[0047] (3) Sb: 3.1-6.0% Sb reduces surface tension by forming fine SnSb. It can also improve tensile strength and tensile strength after aging. If the Sb content exceeds 6.0%, coarse SnSb compounds are precipitated and the fluidity of the molten solder is inhibited, so that the surface tension increases and does not decrease. In addition, the tensile strength after aging is inferior. The upper limit of the Sb content is 6.0% or less, preferably 5.5% or less, more preferably 5.0% or less, and even more preferably 4.5% or less.

[0048] On the other hand, if the Sb content is less than 3.1%, precipitation strengthening is not achieved and solid solution strengthening is insufficient, resulting in deterioration of tensile strength and tensile strength after aging. The lower limit of the Sb content is 3.1% or more, preferably 3.5% or more, more preferably 4.0% or more, and even more preferably 4.1% or more. The preferred range of Sb is 4.1 to 6.0%.

[0049] (4) Bi: 0.1-1.5% Bi can improve wettability by reducing surface tension, and can improve tensile strength and tensile strength after aging by solid solution strengthening. If the Bi content exceeds 1.5%, Bi that exceeds the solid solubility limit segregates and promotes hardening and embrittlement of the solder alloy, resulting in poor tensile strength after aging. The upper limit of the Bi content is 1.5% or less, preferably 1.2% or less, more preferably 1.0% or less, even more preferably 0.9% or less, particularly preferably 0.8% or less, and most preferably 0.7% or less.

[0050] On the other hand, if the Bi content is less than 0.1%, the amount of Bi dissolved becomes insufficient, resulting in poor tensile strength after aging. Also, since the Bi content is low, the surface tension cannot be reduced. The lower limit of the Bi content is 0.1% or more, preferably 0.3% or more, more preferably 0.4% or more, and even more preferably 0.5% or more. The preferred range of Bi is 0.5 to 1.5%.

[0051] (5) In: 0.2-6.0% In contributes to improving tensile strength through solid solution strengthening by dissolving in Sn, and precipitation strengthening by precipitation of InSb, Ag3In, etc. In addition, the inclusion of In in a solder alloy lowers the melting point, lowering the surface tension and contributing to improving wettability. In contributes to the precipitation of various compounds, but the precipitated compounds exhibit fine precipitation behavior, so high wettability is maintained. Furthermore, In contributes to improving tensile strength after aging by controlling the phase transformation of Sn.

[0052] If the In content exceeds 6.0%, the Sn phase undergoes a phase transformation from βSn to γSn, causing the solder alloy to deform and deteriorating the tensile strength after aging. The upper limit of In is 6.0% or less, preferably 5.5% or less, more preferably 5.0% or less, and even more preferably 4.0% or less.

[0053] On the other hand, if the In content is less than 0.2%, the solid solution strengthening is insufficient, and the tensile strength and the tensile strength after aging are deteriorated. In addition, since the In content is small, fine InSb does not precipitate, and the effect of improving wettability is not exhibited. The lower limit of In is 0.2% or more, preferably 0.6% or more, more preferably 1.0% or more, more preferably 2.0% or more, and further preferably 3.0% or more. The preferred range of In is 3.0 to 6.0%.

[0054] (6) Ni: 0.02-0.07% Ni functions as a solidification nucleus when the molten solder solidifies, suppressing supercooling makes the Sn crystal grains fine, and improves the tensile strength after aging. In addition, the precipitation of fine SnNi compounds reduces the surface tension, and at a certain content, the rise in the liquidus temperature can be suppressed. If the Ni content exceeds 0.07%, the precipitation of coarse SnNi compounds inhibits the fluidity of the molten solder, increasing the surface tension and decreasing the wettability. As a result, the tensile strength after aging decreases. Furthermore, the liquidus temperature increases. The upper limit of the Ni content is 0.07% or less, preferably 0.06% or less, and more preferably 0.05% or less.

[0055] On the other hand, if the Ni content is less than 0.02%, the alloy structure will not be refined and the tensile strength after aging will decrease. The lower limit of the Ni content is 0.02% or more, preferably 0.03% or more, and more preferably 0.04% or more. The preferred range of Ni is 0.04 to 0.05%.

[0056] (7) Co: 0.0010~0.0200% Co disperses and precipitates SnCo compounds in the solder alloy, making the alloy structure finer, improving the tensile strength after aging. If the Co content exceeds 0.0200%, the liquidus temperature rises, and the surface tension deteriorates due to the precipitation of coarse SnCo compounds. The upper limit of the Co content is 0.0200% or less, preferably 0.0150% or less, more preferably 0.0120% or less, even more preferably 0.0100% or less, and particularly preferably 0.0090% or less.

[0057] On the other hand, if the Co content is less than 0.0010%, the alloy structure will not be refined and the tensile strength after aging will decrease. The lower limit of the Co content is 0.0010% or more, preferably 0.0030% or more, more preferably 0.0050% or more, even more preferably 0.0060% or more, and particularly preferably 0.0080% or more. The preferred range of Co is 0.0060 to 0.0100%.

[0058] (8) Equations (1) to (4) 0.00029≦Sb×Ni×Co / (Cu×Bi×In)≦0.00151 (1) 0.0039≦Ag×Cu×Sb×In×Ni×Co / Bi≦0.0332 (2) 4.0≦Cu×Sb×In≦20.0 (3) 265≦Ag×Sb / Ni≦499 (4) In the above formulas (1) to (4), Ag, Cu, Bi, Sb, In, Ni, and Co each represent the content (mass %) of the alloy composition.

[0059] The elements constituting the solder alloy according to the present invention have liquidus and solidus temperatures comparable to those of conventional solder alloys, reduce surface tension, and contribute to improving tensile strength and tensile strength after aging. In order to simultaneously exert these effects at a high level with one composition, it is more preferable that each of the constituent elements is within the above-mentioned range, and furthermore that the formulas (1) to (4) are satisfied. The technical meaning of each formula is as follows.

[0060] Formula (1) is a relational expression that takes into consideration the contents of the element group whose wettability deteriorates when the content exceeds the upper limit, and the contents of the element group whose wettability deteriorates when the content falls below the lower limit. Formula (2) is a relational expression that takes into consideration the contents of the element group that forms a compound, and the contents of the elements that do not form a compound. Formula (3) is a relational expression that takes into consideration the contents of the element group that contributes to the tensile strength. Formula (4) is a relational expression that takes into consideration the contents of three elements: Ag, which contributes to improving the tensile strength after aging; Ni, which suppresses the rise in the liquidus temperature and contributes to improving the tensile strength after aging; and Sb, which is contained in a larger amount than before and contributes to reducing the surface tension and improving the tensile strength and the tensile strength after aging.

[0061] Formulas (1) to (4) are formulas that cover all the essential elements that constitute the solder alloy of the present invention. As described above, a solder alloy that satisfies each formula can exert the effects of the present invention at a higher level with just one composition.

[0062] The upper limit of formula (1) is preferably 0.00151 or less, more preferably 0.00114 or less, even more preferably 0.00109 or less, even more preferably 0.00091 or less, particularly preferably 0.00080 or less, most preferably 0.00076 or less, and may be 0.00069 or less, 0.00065 or less, or 0.00063 or less. The lower limit of formula (1) is preferably 0.00029 or more, more preferably 0.00030 or more, even more preferably 0.00032 or more, even more preferably 0.00034 or more, particularly preferably 0.00037 or more, most preferably 0.00038 or more, and may be 0.00040 or more, 0.00046 or more, 0.00048 or more, 0.00053 or more, 0.00055 or more, or 0.00057 or more. A more preferable range of the formula (1) is 0.00037 to 0.00109. The above upper and lower limits can each define a further preferable range of the formula (1).

[0063] The upper limit of formula (2) is preferably 0.0332 or less, more preferably 0.0286 or less, even more preferably 0.0272 or less, even more preferably 0.0238 or less, particularly preferably 0.0228 or less, particularly preferably 0.0224 or less, most preferably 0.0218, and may be 0.0202 or less, 0.0190 or less. The lower limit of formula (2) is preferably 0.0039 or more, more preferably 0.0076 or more, even more preferably 0.0095 or more, even more preferably 0.0114 or more, particularly preferably 0.0118 or more, particularly preferably 0.0127 or more, most preferably 0.0143 or more, and may be 0.0152 or more, 0.0156 or more, 0.0159 or more, 0.0163 or more, 0.0168 or more, or 0.0179 or more. A more preferable range of the formula (2) is 0.0152 to 0.0272. The above upper and lower limits can each define a further preferable range of the formula (2).

[0064] The upper limit of formula (3) is preferably 20.0 or less, more preferably 17.5 or less, even more preferably 15.0 or less, and even more preferably 14.4 or less. The lower limit of formula (3) is preferably 4.0 or more, more preferably 7.0 or more, even more preferably 10.5 or more, even more preferably 10.9 or more, and particularly preferably 14.0 or more. A more preferable range of the formula (3) is 10.5 to 17.5. The above upper and lower limits can each define a further preferable range of the formula (3).

[0065] The upper limit of formula (4) is preferably 499 or less, more preferably 450 or less, even more preferably 425 or less, even more preferably 400 or less, and particularly preferably 375 or less. The lower limit of formula (4) is preferably 265 or more, more preferably 283 or more, even more preferably 340 or more, and even more preferably 348 or more. A more preferable range of the formula (4) is 340 to 425. The above upper and lower limits can each define a further preferable range of the formula (4).

[0066] The values ​​shown in Tables 1 and 2, which are the measured values ​​of the alloy composition, were used to calculate the formulas (1) to (4). The values ​​calculated from the formulas (1) to (4) are calculated to the fifth decimal place for the formula (1), to the fourth decimal place for the formula (2), to the first decimal place for the formula (3), and to an integer value for the formula (4). This calculation rule is used in this application, and is intended to be used in calculations for further solder alloys described in other documents, etc., as all solder alloys must be treated in the same manner.

[0067] (9) At least one of the following elements, in mass percent, is 0.1% or less in total: Ge, Ga, As, Pd, Mn, Zn, Zr, and Mg The solder alloy according to the present invention may contain optional elements within the range that does not impair the effect of the present invention. The effect of the present invention is maintained as long as the total amount of these optional elements is 0.1% or less.

[0068] (10) Remainder: Sn The balance of the solder alloy according to the present invention is Sn. In addition to the above elements, inevitable impurities may be contained. The balance of the solder alloy according to the present invention may consist of Sn and inevitable impurities. Even if inevitable impurities are contained, the above-mentioned effects are not affected.

[0069] The surface tension value evaluated in the present invention is a static surface tension, and is evaluated using a pendant drop method. In the pendant drop method adopted in the present invention, a liquid is pushed out from the tip of a tube (needle), and the surface tension is calculated from the shape of a droplet formed at the tip of the needle. In the conventional method of determining the contact angle with Cu, the measured value varies depending on the surface properties of Cu, etc., so the surface tension of the solder alloy itself was not measured. However, in the present invention, the wettability of the solder alloy itself can be evaluated by measuring the surface tension of the solder alloy itself, which does not depend on the material or surface properties of the electrode. In the solder alloy according to the present invention, if the surface tension is 0.515 N / m or less, the solder alloy can be sufficiently wetted by the electrode, and if it is more than 0.515 to 0.535 N / m or less, the solder alloy can be wetted by the electrode without any problems. If it exceeds 0.535 N / m, the wettability is poor.

[0070] 2. Solder paste The solder paste according to the present invention is a mixture of solder powder having the above-mentioned alloy composition and flux. The flux used in the present invention is not particularly limited as long as it allows soldering by a normal method. Therefore, a suitable mixture of commonly used rosin, organic acid, activator, and solvent may be used. The blending ratio of the metal powder component and the flux component in the present invention is not particularly limited, but is preferably 70 to 90 mass % of the metal powder component and 10 to 30 mass % of the flux component.

[0071] 3. Solder balls The solder alloy according to the present invention can be used as a solder ball. When used as a solder ball, the solder alloy according to the present invention can be manufactured into a solder ball by a dropping method, which is a common method in the industry. Also, a solder joint can be manufactured by processing the solder ball by a common method in the industry, such as mounting one solder ball on one electrode coated with flux and joining the solder ball. The particle size of the solder ball is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. The upper limit of the particle size of the solder ball is preferably 3000 μm or less, more preferably 1000 μm or less, even more preferably 800 μm or less, and particularly preferably 600 μm or less.

[0072] 4. Solder preform The solder alloy according to the present invention can be used as a preform, which may be in the form of a washer, ring, pellet, disk, ribbon, wire, or the like.

[0073] 5. Solder joints The solder joint according to the present invention is suitable for use in joining at least two or more members to be joined. The members to be joined are not particularly limited as long as they are electrically connected using the solder alloy according to the present invention, and include, for example, elements, substrates, electronic components, printed circuit boards, insulating substrates, heat sinks, lead frames, semiconductors using electrode terminals, power modules, inverter products, and the like.

[0074] The solder alloy according to the present invention may be used for bonding in a conventional manner, for example, by using a reflow method. The melting temperature of the solder alloy when performing flow soldering may be about 20°C higher than the liquidus temperature. Furthermore, when using the solder alloy according to the present invention for bonding, the alloy structure can be made finer by taking into consideration the cooling rate during solidification. For example, the solder joint is cooled at a cooling rate of 2 to 3°C / s or more. Other bonding conditions can be appropriately adjusted depending on the alloy composition of the solder alloy.

[0075] 6. In-vehicle electronic circuit, ECU electronic circuit, in-vehicle electronic circuit device, ECU electronic circuit device The solder alloy according to the present invention may be used for soldering electronic circuits mounted on automobiles.

[0076] Examples of electronic components that make up such electronic circuits include chip resistor components, multiple resistor components, QFP, QFN, power transistors, diodes, capacitors, etc. Electronic circuits incorporating these electronic components are mounted on a substrate to form an electronic circuit device.

[0077] In the present invention, the substrate constituting such an electronic circuit device, for example, a printed wiring board, is not particularly limited. The material is also not particularly limited, but a heat-resistant plastic substrate (e.g., FR-4 with high Tg and low CTE) is an example. As the printed wiring board, a printed wiring board in which the surface of Cu land is treated with an organic substance (OSP: Organic Surface Protection) such as amine or imidazole is preferable.

[0078] 7. Other The solder alloy according to the present invention can be manufactured by using a low alpha radiation material as its raw material, and when such a low alpha radiation alloy is used to form solder bumps around a memory, it is possible to suppress soft errors. EXAMPLES

[0079] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples. In order to verify the effects of the present invention, the solder alloys shown in Tables 1 and 2 were used to evaluate (1) solidus temperature and liquidus temperature, (2) surface tension, (3) tensile strength, and (4) tensile strength after aging.

[0080] (1) Solidus and liquidus temperatures For the solder alloys having each alloy composition shown in Tables 1 and 2, the respective temperatures were obtained from the DSC curves. The DSC curves were obtained by heating at 5°C / min in air using a Seiko Instruments DSC (model number: Q2000). The liquidus temperature was obtained from the obtained DSC curves and used as the melting temperature. The solidus temperature was also evaluated from the DSC curves. When the solidus temperature was 205°C or higher and less than 230°C, it was judged as "◎". When the liquidus temperature was 230°C or higher and less than 246°C, it was judged as "◯". When the liquidus temperature was 246°C or higher, it was judged as "X".

[0081] (2) Surface tension For the solder alloys having each alloy composition shown in Tables 1 and 2, a contact angle meter (Model DM-700, manufactured by Kyowa Interface Science Co., Ltd.) was used to measure by the pendant drop method in a nitrogen atmosphere (oxygen concentration 2000 ppm or less) at 250°C. The surface tension formed was determined using an image processing type solid-liquid interface analysis system DropMaster 500 manufactured by Kyowa Interface Science Co., Ltd. Surface tensions of 0.515 N / m or less were judged as "◎", those exceeding 0.515 N / m and 0.535 N / m or less were judged as "◯", and those exceeding 0.535 N / m were judged as "×".

[0082] (3) Tensile strength The tensile strength was measured according to JIS Z3198-2. For each solder alloy listed in Tables 1 and 2, a test piece with a gauge length of 30 mm and a diameter of 8 mm was prepared by casting into a mold. The prepared test piece was pulled at room temperature with a stroke of 6 mm / min using an Instron Type 5966, and the strength at which the test piece broke was measured. In addition, the reduction in area was measured from the ratio of the cross-sectional area S1 of the broken part of the test piece to the cross-sectional area S0 before the test. When the tensile strength was 90 MPa or more, it was evaluated as "◎", when it was 85 MPa or more and less than 90 MPa, it was evaluated as "◯", and when it was less than 85 MPa, it was evaluated as "X".

[0083] (4) Tensile strength after aging Test pieces similar to those in "(3) Tensile strength" were prepared and aged in a thermostatic chamber in air at 105°C for 200 hours. The test pieces after aging were subjected to a tensile test in a 105°C environment similar to "(3) Tensile strength". Tensile strengths of 43 MPa or more were judged as "◎", those between 42 MPa and 43 MPa were judged as "◯", and those less than 42 MPa were judged as "×".

[0084] [Table 1]

[0085] [Table 2]

[0086] As is clear from Tables 1 and 2, in Examples 1 to 48, the contents of the essential elements Ag, Cu, Sb, Bi, In, Ni, and Co were all within the range of the present invention, and therefore all were evaluated as "good" or "excellent." In particular, in Examples 1 to 4, 7, 8, 11, 12, 17 to 19, 24 to 29, 33, 34, 37, 38, and 40 to 48, which satisfy formulas (1) to (4), all were evaluated as "good," indicating superior results among the Examples.

[0087] On the other hand, in Comparative Example 1 and Comparative Example 2, the Ag content was not appropriate, so the tensile strength after aging was poor. In Comparative Example 3, the Cu content was low, so the surface tension, tensile strength, and tensile strength after aging were poor. In Comparative Example 4, the Cu content was high, so the tensile strength after aging was poor.

[0088] In Comparative Example 5, the Sb content was low, so the tensile strength and tensile strength after aging were poor. In Comparative Example 6, the Sb content was high, so the surface tension and tensile strength after aging were poor. In Comparative Examples 7 to 9, the Bi content was low or no Bi was contained, so the surface tension and tensile strength after aging were poor. In Comparative Example 10, the Bi content was high, so the tensile strength after aging was poor.

[0089] In Comparative Example 11, the surface tension, tensile strength, and tensile strength after aging were poor because of the low In content. In Comparative Example 12, the tensile strength after aging was poor because of the high In content. In Comparative Example 13, the tensile strength after aging was poor because of the low Ni content. In Comparative Example 14, the liquidus temperature was high and the surface tension and tensile strength after aging were poor because of the high Ni content.

[0090] Comparative Example 15 had poor tensile strength after aging due to the low Co content, whereas Comparative Example 16 had a high Co content, resulting in an increased liquidus temperature and poor surface tension.

[0091] The results of observing the cross section after the tensile strength test are shown in Fig. 1 and Fig. 2. Fig. 1 is an SEM photograph of the cross section after the tensile strength test enlarged by 1000 times, Fig. 1(a) is Comparative Example 12, Fig. 1(b) is Example 3, and Fig. 1(c) is Example 25. Fig. 2 is an SEM photograph of Fig. 1 enlarged by 3000 times, Fig. 2(a) is Comparative Example 12, Fig. 2(b) is Example 3, and Fig. 2(c) is Example 25. As is clear from Fig. 1 and Fig. 2, it was found that InSb and Ag3(Sn,In) were precipitated in Example 3 and Example 25. On the other hand, it was found that InSb and Ag3(Sn,In) were coarsened in Comparative Example 12 because of the large amount of In.

[0092] Table 3 below shows the wettability results evaluated in this embodiment and the evaluation results using the conventional meniscograph method for examples and comparative examples arbitrarily selected from Tables 1 and 2.

[0093] The meniscograph method was evaluated as follows: (1) Preparation of test panels Flux ("ES-1100" manufactured by Senju Metal Industry Co., Ltd.) was applied to a copper plate (width 10 mm x length 30 mm x thickness 0.3 mm). The flux-applied copper plate was heat-treated at 120°C for 15 minutes in an air atmosphere to obtain a test plate. Five such test plates were prepared for each of the examples and comparative examples shown in Table 3.

[0094] (2) Evaluation method The obtained test plates were immersed in a solder bath containing molten solder having the alloy composition shown in Table 3, and the zero cross time (sec) was obtained. Here, a Solder Checker SAT-5100 (manufactured by RHESCA) was used as the test device, and the evaluation was performed as follows. Solder wettability was evaluated based on the average value of the zero cross time (sec) of the five test plates of each example and each comparative example. The test conditions were set as follows.

[0095] Immersion speed in solder bath: 10mm / sec Immersion depth in solder bath: 4mm Immersion time in solder bath: 10 sec Solder bath temperature: 255℃ The shorter the average value of the zero cross time (sec), the faster the wetting speed, which means better solder wettability.

[0096] (3) Judgment criteria If the average zero cross time (sec) was 1.2 seconds or less, it was judged as "◎", if it was more than 1.2 seconds but less than 1.3 seconds, it was judged as "◯", and if it was more than 1.3 seconds, it was judged as "X".

[0097] [Table 3]

[0098] As is clear from Table 3, it was found that the meniscograph method and the pendant drop method evaluated in this example sometimes produce different evaluation results. In addition, even if an alloy composition is evaluated as "◎" by the meniscograph method, it is evaluated as "◯" by the pendant drop method. Therefore, it was found that the pendant drop method evaluated in this example can directly evaluate the wettability of the molten solder itself, and therefore can evaluate wettability more strictly.

Claims

1. A solder alloy having an alloy composition, in mass %, of 3.0 to 4.0% Ag, 0.1 to 1.0% Cu, 3.1 to 6.0% Sb, 0.1 to 1.5% Bi, 0.2 to 6.0% In, 0.02 to 0.07% Ni, 0.0010 to 0.0200% Co, and the balance being Sn (excluding alloy compositions of 3.0% Ag, 0.7% Cu, 4.0% Sb, 1.5% Bi, 2.5% In, 0.04% Ni, 0.01% Co, and the balance being Sn), wherein the alloy composition satisfies all of the following formulas (1) to (4): 0.00029≦Sb×Ni×Co / (Cu×Bi×In)≦0.00151 (1) 0.0039≦Ag×Cu×Sb×In×Ni×Co / Bi≦0.0332 (2) 4.0≦Cu×Sb×In≦20.0 (3) 265≦Ag×Sb / Ni≦499 (4) In the above formulas (1) to (4), Ag, Cu, Bi, Sb, In, Ni, and Co each represent the content (mass %) of the alloy composition.

2. 2. The solder alloy according to claim 1, wherein the alloy composition further contains, by mass%, 0.1% or less in total of at least one of Ge, Ga, As, Pd, Mn, Zn, Zr, and Mg.

3. A solder paste comprising a solder powder made of the solder alloy according to claim 1 or 2.

4. A solder ball made of the solder alloy according to claim 1 or 2.

5. A solder preform made of the solder alloy according to claim 1 or 2.

6. A solder joint comprising the solder alloy according to claim 1 or 2.

7. An in-vehicle electronic circuit comprising the solder alloy according to claim 1 or 2.

8. 3. An ECU electronic circuit comprising the solder alloy of claim 1 or 2.

9. An on-vehicle electronic circuit device comprising the on-vehicle electronic circuit according to claim 7.

10. An ECU electronic circuit device comprising the ECU electronic circuit according to claim 8.

Citation Information

Patent Citations

  • Pneumatic tire and rim assembly

    JP1978049703A

  • Magnetic-fluid shaft sealing device

    JP1987075178A

  • High Reliability Lead-Free Solder Alloy for Electronic Equipment Applications in Harsh Environments

    JP2018518368A

  • Solder alloy, solder ball, solder preform, solder paste, and solder joint

    JP2023051075A

  • Advanced Solder Alloys For Electronic Interconnects

    US20180102464A1